Pengaturan Hukum Merek Atas Indikasi Geograafis - budi agus riswandi (Fakultas Hukum Universitas Islam Indonesia, 2005)
Trade Mark Law in Indonesia has regulated geographical indication. It means, that Indonesia has already harmonized the regulation to the TRIP's system. However, the existence of the rules has not provided optimum protection to the potential geography in Indonesia. One of the Obstacles is the existence of the implementation nrle to support the enforcement of geographical indication on the Act No. 15/2001 has not yet issued.